A case report of apparent remifentanil resistance in a paediatric patient. Issue 1 (4th June 2016) - Wrigley, Hannah; Murphy, Peter
Summary: We present the case of a three‐year‐old patient undergoing cardiac magnetic resonance imaging who demonstrated a non‐typical response to a remifentanil infusion. Following exclusion of common reasons for apparent remifentanil 'failure', including correct drug preparation and delivery, we consulted the literature for other possible causes. We suggest there may be a sub‐group of patients who are either outliers in the dose response curve or who are truly 'resistant' to certain pharmacodynamic effects of remifentanil in both adult and paediatric practice.